Influence Of Work Motivation, Work Environment And Work Discipline On The Work Productivity Of Employees In Bebek Hi Restaurant. Slamet Bandar Lampung During The Covid-19 Pandemic - Amriyadi, Amriyadi; Ardansyah, Ardansyah (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
Pak Slamet's fried duck restaurant has been around since 1986, Pak Slamet's first stall, standing on the side of the Solo-Yogya road. Initial observations found problems related to employee productivity at Bebek Hi Restaurant. Slamet Bandar Lampung, namely employee productivity which has decreased, one of which is due to the impact of Covid-19 which has an impact on decreasing employee productivity and restaurant income. The purpose of this study was to determine the effect of work motivation, work environment and work discipline on the work productivity of Bebek Hi Restaurant employees. Slamet Bandar Lampung during the Covid-19 pandemic. This study uses quantitative research methods. Data analysis used multiple linear regression analysis. Based on the results of research and discussion, it can be concluded that there partial work motivation on work productivity of Bebek Hi Restaurant employees. Slamet Bandar Lampung. There partial the work environment on the work productivity of Bebek Hi Restaurant employees. Slamet Bandar Lampung. There partial work discipline on the work productivity of Bebek Hi Restaurant employees. Slamet Bandar Lampung. There simultaneous work motivation, work environment and work discipline on work productivity at Bebek Hi Restaurant. Welcome to Bandar Lampung.